The role of genetic testing in evaluating surgical outcomes for pediatric focal cortical dysplasia associated with NPRL3 variant - Bei Li; Liang Liu; Jianyun Su; Shanshan Jia; Zhijing Wang; Xia Li; Siyu Zhao (Epilepsy & Behavior Reports, 2025)
This case report describes a 5-year-and-10-month-old female patient who developed sleep-related hypermotor epilepsy, at the age of 2, exhibiting various forms of seizures since the age of 2. Initially, the seizures were controlled for one year with multiple anti-seizure medications; however, symptoms recurred when the patient was 3 years and 5 months old, leading to an increased seizure frequency and a poor response to combined drug therapy. Long-term video-EEG revealed discharges originating from the frontal lobe, while MRI and PET-CT scans indicated FCD in the left frontal region. The patient underwent left frontal epileptogenic focus resection at the age of 6, with pathological findings confirming FCD type 1b. Whole-exome sequencing of blood and brain tissue samples revealed NPRL3 gene variants. Although she remained seizure-free for one year post-surgery, the patient experienced a relapse, with follow-up EEG revealing multifocal discharges. These findings indicate that variants in the NPRL3 gene contribute to focal cortical dysplasia (FCD) and are frequently associated with drug-resistant epilepsy. For FCD 1b patients with NPRL3 gene variants, the risks and benefits of surgery should be carefully evaluated. This report explores the role of NPRL3 gene variants in FCD1b and their impact on surgical treatment, emphasizing the importance of comprehensive preoperative assessment and individualized therapeutic strategies.